2020
DOI: 10.4269/ajtmh.20-0722
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: COVID-19 with Bilateral Adrenal Hemorrhage

Abstract: . A 70-year-old Dominican Republic man presented with lower back pain for 10 days. Fifteen days before pain onset, he had low-grade fever, chills, and asthenia, and 4 days before admission, he had constipation, malaise, generalized weakness, anorexia, nausea, and vomiting. On admission, the patient was afebrile and hypotensive, with a heart rate of 105 and an oxyhemoglobin saturation on room air of 95%. Hyponatremia, lymphopenia, elevated C-reactive protein, and ferritin were observed in complementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 8 publications
2
29
0
3
Order By: Relevance
“…Finally, this case series besides other intraperitoneal bleeding reports in COVID-19 patients [10,11,20,21] demonstrated that COVID-19 coagulopathy and AT should be studied more. To reduce the disease mortality and morbidity investigations on the pathophysiology of COVID-19-associated coagulopathy and finding the best intervention to prevent or treat it is needed.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Finally, this case series besides other intraperitoneal bleeding reports in COVID-19 patients [10,11,20,21] demonstrated that COVID-19 coagulopathy and AT should be studied more. To reduce the disease mortality and morbidity investigations on the pathophysiology of COVID-19-associated coagulopathy and finding the best intervention to prevent or treat it is needed.…”
Section: Discussionsupporting
confidence: 54%
“…Hemophagocytic lymphohistiocytosis (HLH) could cause coagulation disorders leading to hemorrhage [ 6 ] and there is some evidence that hyper-inflammation state could induce HLH in COVID-19 patients [ 7 ], but clinical manifestation and laboratory markers (fever, splenomegaly, decreased counts in two cell lines, hypertriglyceridemia and/or hypofibrinogenemia, and hemophagocytosis) of our patients did not make this diagnosis as the H-score for our patient were less than 90. Catastrophic APS is a rare autoimmune disease that could cause coagulation disturbance by increasing aPTT and there is some controversial evidence about its occurrence in critically ill patients with COVID-19 [ 8 , 9 ]; there are also two cases of COVID-19 bilateral adrenal hemorrhage that one of them had a history of antiphospholipid syndrome and the other one had a suspected history of autoimmune diseases [ 10 , 11 ], however, unfortunately, we did not check markers of this disease but none of our patients developed notable prolonged PTT.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was positive for COVID-19 IgG and IgM. Both basal cortisol and stimulated confirmed the diagnosis of adrenal insufficiency [ 98 ] and intravenous corticosteroid treatment was started followed by oral therapy with subsequent symptom resolution. In these two cases, the presence of underlying autoimmune disease may predispose COVID-19 patients to develop coagulation disorders and disseminated intravascular coagulation (DIC) and thrombosis with subsequent hemorrhage in the most vascularized organs [ 99 ].…”
Section: Resultsmentioning
confidence: 93%
“…A direct negative effect on pituitary corticotroph cells was described during previous SARS outbreak in 2002-2003: according to both basal serum cortisol and dynamic test (especially the low-dose short synacthen test), up to 40% of the cohort was found with an insufficient HPA axis [18]. Recently, a primary adrenal injury consistent with bilateral adrenal haemorrhage has been reported in a patient with Covid-19 infection [19].…”
Section: Risk Of Adrenal Insufficiency In Patients With Covid-19mentioning
confidence: 97%